A randomized placebo-controlled trial to investigate the effect of lactolycopene on semen quality in healthy males. - Williams, Elizabeth A.; Parker, Madeleine; Robinson, Aisling; Pitt, Sophie; Pacey, Allan A. (European Journal of Nutrition, 2020)
Purpose: Poor sperm quality is a major contributor to infertility in heterosexual couples, but at present there are few empirical therapies. Several studies have examined the role of dietary factors and data from randomized controlled trials suggest that oral antioxidant therapy can improve some sperm parameters. Health benefits of lycopene supplementation have been proposed for a variety of health conditions and here we examine whether it can help improve sperm quality. This study aimed to investigate the effect of 14 mg daily lactolycopene for 12 weeks on semen quality in healthy men. Methods: Sixty healthy male participants were recruited and randomized to this double-blind, placebo-controlled parallel study and received either 14 mg/d lactolycopene or a placebo for 12 weeks. The primary endpoint was a change in motile sperm concentration. Secondary endpoints were all other aspects of sperm quality, including the level of sperm DNA damage. Results: Fifty-six men completed the intervention and the level of plasma lycopene was significantly increased in the men randomized to receive lycopene supplementation. There was no significant change in the primary endpoint (motile sperm concentration) post-intervention (p = 0.058). However, the proportion of fast progressive sperm (p = 0.006) and sperm with normal morphology (p < 0.001) did improve significantly in response to lactolycopene intervention. Conclusions: Supplementation with 14 mg/d lactolycopene improves sperm motility and morphology in young healthy men. Clinical Trial Registry number and website: ISRCTN33248724 http://www.isrctn.com/ISRCTN33248724